Herbicide Widespread: The Effects of Pethoxamid on Nonalcoholic Fatty Liver Steatosis In Vitro - Anna Virginia Adriana Pirozzi; Antonietta Stellavato; Chiara Schiraldi; Mariateresa Giuliano (Journal of Toxicology)
Pethoxamid is a widespread herbicidal product, presenting itself as an extremely flexible active substance and with a high potential for use as an herbicide for preemergence. The emergence of multiple resistance in crops has been addressed using combinations of preemergence and postemergence herbicides in the same seeding-harvest cycle. A winning combination of pethoxamid and glyphosate mainly affected the acidobacteria population. Glyphosate scientific literature has demonstrated an observational link between herbicide exposure and liver disease in human subjects. Identifying and ranking the risk to the public that pethoxamid could exert on target organs has not been evaluated so far. Due to similarities to glyphosate, we did look at the effect of pethoxamid on impaired liver cells HepG2, using a nonalcoholic fatty liver disease (NAFLD) cell model in vitro. Pethoxamid was cytotoxic starting at 1 ppm. Fatty acid accumulation (FA) was enhanced while low doses of pethoxamid slightly decreased LDH protein expression compared to FA-treated HepG2. The same trend was observed for cytochrome c. Based on our data, we can argue that NAFLD hepatic cells react to pethoxamid trying detoxifying strategies, ready to undergo cell death to avoid further degeneration. Downregulation of cytochrome can lead to the hypothesis that pethoxamid should not induce herbicide resistance.